The impact of talent management practices on teacher retention: A case study of Darunnajah Islamic Boarding School - Dona Dilova; Engga Jalaludin; Samiyono Samiyono (Privietlab, 2025)
This study examines how talent management practices impact teacher retention at Darunnajah Islamic Boarding School. The examined practices in talent management encompass recruitment and selection processes, teamwork and managerial support, performance and career management, salary and compensation, teacher engagement, and the working conditions. This study employs a quantitative methodology utilizing the Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis technique. Data collection involved administering questionnaires to educators who had served for at least one year in their current position. The findings demonstrate that performance and career management, along with working conditions, significantly and positively influence teacher retention. Conversely, the factors of recruitment and selection processes, teamwork and managerial support, salary and compensation, and teacher engagement do not significantly impact teacher retention. The results indicate that teachers’ retention is primarily affected by internal elements associated with opportunities for self-development and a supportive work environment rather than by administrative or financial considerations. This study aims to offer significant insights for decision-makers in Islamic boarding schools, assisting them in crafting more focused talent-management strategies to retain exceptional educators.